PENGARUH LATIHAN AJAX SHUTTLE DRILL TERHADAP KELINCAHAN PADA PEMAIN SEKOLAH SEPAKBOLA (SSB) U-15 CHEVRON PEKANBARU - Amat Arifin; Slamet '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on observations in the field is known that there are many shortcomings exercise leads to increased agility capabilities . Based on the existing problems , the researchers aim to provide a form of exercise that can increase agility and providing intensive training program . In this study the authors only focus on one form of exercise that is training agility drill Ajax Shuttle Drill for this form of exercise has never been attempted on a football school athletes ( SSB ) U-15 Chevron Pekanbaru. This study used an experimental method , in order to determine the effect of exercise . Thus the experimental research method can be interpreted as a method of research that is useful to search for a specific treatment effect against the other in uncontrolled conditions . The first step taken is to Pree -test that tests Illinois Agility Test . To measure the agility of the athletes before training . Furthermore, the samples are given treatment that Ajax Shutlle Drill exercises , and conducted final tests that Post - Pest with the Illinois Agility Test. To see if there is improvement after the treatment was given treatment . Data were analyzed descriptively , then further testing research hypotheses have been proposed to fit the problem is: there is the influence of exercise Ajax Shuttle Drill significant agility. bedasarkan t test analysis produces T count of 14.71dan Ttable 1.77 . Tmeans the arithmetic> Ttable .We can conclude that H0 is rejected Ha accepted . So it can be summed up as follows : there is a shuttle ajax exercise influence on the agility drill at school football player (SSB) U-15 chevron pekanbaru .Keywords : Exercise ajax shuttle drill, agility2